Household choices and child development - Daniela Del Boca; Christopher Flinn; Matthew Wiswall (Institute for the Study of Labor (IZA), 2010)
The growth in labor market participation among women with young children has raised concerns about the potential negative impact of the mother's absence from home on child outcomes. Recent data show that mother's time spent with children has declined in the last decade, while the indicators of children's cognitive and noncognitive outcomes have worsened. The objective of our research is to estimate a model of the cognitive development process of children nested within an otherwise standard model of household life cycle behavior. The model generates endogenous dynamic interrelationships between the child quality and employment processes in the household, which are found to be consistent with patterns observed in the data. The estimated model is used to explore the effects of schooling subsidies and employment restrictions on household welfare and child development.
Keywords: J13; D1; 330; time allocation; child development; household labor supply; Mütter; Frauenerwerbstätigkeit; Familienökonomik; Kinder; Kognitive Fähigkeiten; Schätzung; USA